(untitled) (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2023)
Risk management plays a vital role in portfolio analysis. It requires adequate knowledge in finance and application of sophisticated techniques. In the allocation of fund analysis, Markowitz mean-variance model is the most popular one. Later, Sharpe’s single index model and arbitrage pricing theory have been developed. But all these techniques have not considered the risk perception and risk propensity of the investors. Risk perception of the investor depends on so many factors and it ultimately affect risk propensity of the investors (value system of the investors). In this study an attempt has been taken to analyse the approaches of allocation of fund based on the risk propensity of the investors. The study is conducted on taking NIFTY 50 securities. Finally the results of different approaches are compared with the results of the Markowitz mean –variance portfolio optimisation.